2013
DOI: 10.1371/journal.pone.0079755
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Results of a Minimally Invasive Surgical Pulmonary Vein Isolation and Ganglionic Plexi Ablation for Atrial Fibrillation

Abstract: BackgroundGanglionated plexi (GP) ablation has been become an adjunct to pulmonary vein isolation (PVI). This study describes the long-term results of minimally invasive surgical PVI, ablation of GPs, and exclusion of the left atrial appendage for atrial fibrillation (AF).MethodsLong-term follow-up of 55 months was performed in 139 consecutive patients (age 58.3±20.8 years) with symptomatic, drug-refractory lone AF who underwent minimally invasive surgical PVI, GPs ablation, and exclusion of the left atrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
4
27
0
3
Order By: Relevance
“…Conversely, outcomes with PVI-GP ablation seem to not be as favorable in patients with persistent or LSPAF. In 2013, Zheng et al, revealed at approximately 5 years follow up, the success rate for surgical PVI-GP ablation was 51.8% for paroxysmal AF, 28.2% for persistent AF, and 28.6% for LSPAF (21). Thus, the influence of the autonomic nervous system on LSPAF remains uncertain.…”
Section: Autonomic Remodelingmentioning
confidence: 99%
“…Conversely, outcomes with PVI-GP ablation seem to not be as favorable in patients with persistent or LSPAF. In 2013, Zheng et al, revealed at approximately 5 years follow up, the success rate for surgical PVI-GP ablation was 51.8% for paroxysmal AF, 28.2% for persistent AF, and 28.6% for LSPAF (21). Thus, the influence of the autonomic nervous system on LSPAF remains uncertain.…”
Section: Autonomic Remodelingmentioning
confidence: 99%
“…The lack of standardized lesion sets and long-term follow-up data make it difficult to predict which patients will benefit from the other minimally invasive ablation procedures, but in general these techniques have had greater success in patients with short-duration paroxysmal AF and small left atria (LA) (6,7). Pulmonary vein isolation can be considered in selected patients with paroxysmal AF and LA diameter <4.5 cm, and can be performed via a minimally invasive video-assisted or completely thoracoscopic approach without CPB (6,8).…”
Section: Indications For Surgical Af Ablationmentioning
confidence: 99%
“…However, to date, these approaches have only been performed at specialized centers and with limited patient follow-up. The addition of surgical or catheter-based ganglionated plexus ablation has been proposed to improve the outcomes of these lesion sets, although the subset of patients that benefit from this addition has yet to be clearly identified (7,9). At our center, ganglionated plexus ablation is never performed due to the absence of clinical trials showing benefit and the ubiquitous and inevitable reinnervation that occurs in both animals and humans (10).…”
Section: Indications For Surgical Af Ablationmentioning
confidence: 99%
“…Minimally invasive approaches have also been utilized in conjunction with treatment for AF, with bilateral video-assisted thoracoscopic pulmonary vein isolation, atrial ganglia ablation, ligament of Marshall division and LAA staple excision, with a reported success rate of 50 -90% in maintaining sinus rhythm for paroxysmal AF, 30 -85% for persistent AF and 30 -75% for long-standing persistent AF, [117][118][119] and up to 90% if followed by a "touch-up" catheter ablation procedure. 120 The effects on stroke risk reduction of these hybrid approaches is currently unknown.…”
Section: Minimally Invasive and Hybrid Surgical Approachesmentioning
confidence: 99%